Extending a Single Residue Switch for Abbreviating Catalysis in Plant ent-Kaurene Synthases - Jia, Meirong; Peters, Reuben J. (Frontiers in Plant Science, 2016)
Production of ent-kaurene as a precursor for important signaling molecules such as the gibberellins seems to have arisen early in plant evolution, with corresponding cyclase(s) present in all land plants (i.e., embryophyta). The relevant enzymes seem to represent fusion of the class II diterpene cyclase that produces the intermediate ent-copalyl diphosphate (ent-CPP) and the subsequently acting class I diterpene synthase that produces ent-kaurene, although the bifunctionality of the ancestral gene is only retained in certain early diverging plants, with gene duplication and sub-functionalization leading to distinct ent-CPP synthases (CPSs) and ent-kaurene synthases (KSs) generally observed. This evolutionary scenario implies that plant KSs should have conserved structural features uniquely required for production of ent-kaurene relative to related enzymes that have alternative function. Notably, substitution of threonine for a conserved isoleucine has been shown to “short-circuit” the complex bicyclization and rearrangement reaction catalyzed by KSs after initial cyclization, leading to predominant production of ent-pimaradiene, at least in KSs from angiosperms. Here this effect is shown to extend to KSs from earlier diverging plants (i.e., bryophytes), including a bifunctional CPS/KS. In addition, attribution of the dramatic effect of this single residue “switch” on product outcome to electrostatic stabilization of the ent-pimarenyl carbocation intermediate formed upon initial cyclization by the hydroxyl introduced by threonine substitution has been called into question by the observation of similar effects from substitution of alanine. Here further mutational analysis and detailed product analysis is reported that supports the importance of electrostatic stabilization by a hydroxyl or water.